The economic value of the wildlife trade in Vietnam - Pham Thu Thuy; Trần, Y.L.; Nguyễn Thị, K.N.; Tăng Thị, K.H.; Đặng, H.P. (Center for International Forestry Research, 2021)
Wildlife farming generates significant earnings for many households in many provinces, and creates employment opportunities for the rural workforce. The fact that many households in many provinces depend on wildlife farming as their main source of income also creates major challenges for wildlife conservation and management.